2000
DOI: 10.1152/ajprenal.2000.279.2.f326
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin inhibits thick ascending limb chloride flux via ETBreceptor-mediated NO release

Abstract: Endothelin-1 (ET-1) inhibits transport in various nephron segments, and the thick ascending limb of the loop of Henle (TALH) expresses ET-1 receptors. In many tissues, activation of ET(B) receptors stimulates release of NO, and we recently reported that endogenous NO inhibits TALH chloride flux (J(Cl)). However, the relationship between ET-1 and NO in the control of nephron transport has not been extensively studied. We hypothesized that ET-1 decreases NaCl transport by cortical TALHs through activation of ET(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 46 publications
(49 reference statements)
6
106
1
2
Order By: Relevance
“…9,32,33 Despite these effects, this and previous studies demonstrate that rats genetically deficient in ET B or undergoing chronic ET B blockade exhibit saltsensitive hypertension responsive to ET A blockade, suggesting that Na retention and hypertension under these conditions results not from a lack of ET B -mediated natriuresis or diuresis in the kidney but from an increase in ET A signaling. 11,15 This study goes further to demonstrate that although intrarenal ET B plays a significant role in determining BP in these animals on DNa diet, it plays a relatively minor role in determining BP in these animals on HNa diet.…”
Section: Perspectivesmentioning
confidence: 51%
“…9,32,33 Despite these effects, this and previous studies demonstrate that rats genetically deficient in ET B or undergoing chronic ET B blockade exhibit saltsensitive hypertension responsive to ET A blockade, suggesting that Na retention and hypertension under these conditions results not from a lack of ET B -mediated natriuresis or diuresis in the kidney but from an increase in ET A signaling. 11,15 This study goes further to demonstrate that although intrarenal ET B plays a significant role in determining BP in these animals on DNa diet, it plays a relatively minor role in determining BP in these animals on HNa diet.…”
Section: Perspectivesmentioning
confidence: 51%
“…The extent to which the antinatriuresis associated with medullary NOS inhibition was a direct consequence of reduction of MBF (16,102) or was related to changes of intrarenal paracrine/autocrine systems (95,100) or was a direct consequence of tubular epithelial transport actions of NO (80,136) awaited a better understanding of the intrarenal sites of NO production. Initial efforts to determine regional NO biosynthesis by determining tissue nitrite/nitrate and cGMP levels in slices of dissected renal zones, isolated glomeruli, and various cell cultures systems.…”
Section: Localization Of No Production Within Vascular and Tubular Stmentioning
confidence: 99%
“…Taylor et al 65 found that in ET B receptor-deficient rats, medullary NOS activity and renal endothelin production are decreased, indicating that renal endothelin regulates NOS 3 activity as reported for the thick ascending limb. 66 Mori et al 67 found that vasopressin stimulated a rapid increase in intracellular NO via increased intracellular calcium levels in the inner medullary collecting duct. Although they did not assess which NOS isoform was activated, NOS 3 is likely responsible because of its high expression in the collecting duct.…”
Section: Hormonal Regulation Of Nosmentioning
confidence: 99%